2005
DOI: 10.1128/jvi.79.10.6281-6290.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Cell Type-Specific Poliovirus Propagation in HEK 293 Cells

Abstract: The ability of poliovirus to propagate in neuronal cells can be reduced by introducing appropriate nucleotide substitutions into the viral genome. Specific mutations scattered throughout the poliovirus genome yielded the live attenuated vaccine strains of poliovirus. Neuron-specific propagation deficits of the Sabin strains are partially encrypted within a confined region of the internal ribosomal entry site (IRES), which carries attenuating point mutations in all three serotypes. Recently, high levels of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 56 publications
6
82
0
Order By: Relevance
“…This, coupled with a large excess of positivestrand RNA production, may explain the recovery of viral growth at a later time in infection. In similar studies of poliovirus, in which the IRES was replaced with that of HRV2, no significant difference in virus growth or translation was observed in nonneuronal cells (6,17). We found that the PV1M 5= UTR was less efficient in controlling cap-independent translation than the HEV71 5= UTR in luciferase reporter assays (data not shown).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This, coupled with a large excess of positivestrand RNA production, may explain the recovery of viral growth at a later time in infection. In similar studies of poliovirus, in which the IRES was replaced with that of HRV2, no significant difference in virus growth or translation was observed in nonneuronal cells (6,17). We found that the PV1M 5= UTR was less efficient in controlling cap-independent translation than the HEV71 5= UTR in luciferase reporter assays (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Although previous studies in animal models have succeeded in identifying genetic modifications that attenuate the virulence of enteroviruses, including coxsackieviruses and poliovirus (6,11), attempts to understand the underlying mechanism of virulence attenuation have not been undertaken. This is because the replication cycle of picornaviruses involves a series of complex overlapping processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparable study Semler and co-workers deleted the entire 39-UTR of poliovirus and found only a minor defect in viral RNA replication in HeLa cells, but a major replication defect in neuroblastoma cells and a major neurovirulence attenuation in transgenic mice (Todd et al 1995(Todd et al , 1997Brown et al 2004). A cell-type-specific effect of 39-UTR mutations on virus propagation was also reported for HEK 293 cells by Gromeier and collaborators (Campbell et al 2005). A coxsackievirus mutant containing the rhinovirus IRES and a deletion of the Z-domain had wild-type growth characteristics in HeLA cells but was severely impaired in growth in neuroblastoma cells (Campbell et al 2005).…”
Section: Biological Implicationsmentioning
confidence: 75%
“…A cell-type-specific effect of 39-UTR mutations on virus propagation was also reported for HEK 293 cells by Gromeier and collaborators (Campbell et al 2005). A coxsackievirus mutant containing the rhinovirus IRES and a deletion of the Z-domain had wild-type growth characteristics in HeLA cells but was severely impaired in growth in neuroblastoma cells (Campbell et al 2005). We did not detect reduced growth of any mutant in neuroblastoma cells as well.…”
Section: Biological Implicationsmentioning
confidence: 84%